Primary inflammatory myofibroblastic tumor of the diaphragm: Report of a case. Issue 4 (27th October 2013) - Fu, Junke; Wu, Qifei; Zhang, Yong; Zhang, Xufeng; Wang, Zhe
Abstract: We report a case of primary inflammatory myofibroblastic tumor of the diaphragm in a 64‐year‐old man. The patient was hospitalized for a computed tomography (CT)‐detected large tissue mass at the left lower lung field. Complete tumor excision followed by pathological investigation was performed. Microscopically, the tumor showed staggered arrangements of spindle myoepithelial cells, lymphoblastic and eosinophil cells. Immunohistochemically, the proliferating spindle cells showed positive staining for smooth muscle actin, vimentin, CD68 and Desmin, but negative for cytokeratin, leukocyte common antigen, epithelial membrane antigen, and S‐100. This is the first reported inflammatory myofibroblastic tumor of the diaphragm found in an adult. The postoperative course was uneventful and the patient had no recurrence 18 months after surgery.